Reviewing advancement in Mycoplasma pneumoniae P30 adhesin protein provides insights for future diagnosis and treatment - Zuo, Yingying; Zhang, Ru; Li, Shuihong (Frontiers in Microbiology, 2024)
Mycoplasma pneumoniae is a major pathogen that causes upper and lower respiratory tract infections in children, adolescents, and elderly individuals and can lead to pneumonia, intrapulmonary and extrapulmonary complications, and respiratory sequelae. M. pneumoniae must adhere to respiratory epithelial cells of a host for infection. The P1 and P30 proteins, as two adhesin proteins of M. pneumoniae, have attracted extensive attention from many researchers. In this paper, we present the latest research progress on the P30 protein in terms of structure and mutation typing, physiological function, clinical serological diagnosis and vaccine development in a literature review. This study deepens our knowledge on the pathogenesis of M. pneumoniae and is useful for diagnosing and preventing M. pneumoniae infection.